2014
DOI: 10.1038/ncomms6249
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-assisted chemical vapour deposition of high-performance small-diameter GaSb nanowires

Abstract: Although various device structures based on GaSb nanowires have been realized, further performance enhancement suffers from uncontrolled radial growth during the nanowire synthesis, resulting in non-uniform and tapered nanowires with diameters larger than few tens of nanometres. Here we report the use of sulfur surfactant in chemical vapour deposition to achieve very thin and uniform GaSb nanowires with diameters down to 20 nm. In contrast to surfactant effects typically employed in the liquid phase and thin-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
132
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(148 citation statements)
references
References 55 publications
8
132
2
Order By: Relevance
“…4 While the synthesis, processing, and applications of III-V materials have been studied for more than a decade, research on III-Sb NWs has attracted a growing interest only recently. [5][6][7][8][9] GaSb, in particular, is an increasingly important material for a III-V p-channel metaloxide-semiconductor field-effect transistor (MOSFET) due to its high hole mobility. 10 However, the mobility is highly dependent on the materials synthesis method and device structure.…”
mentioning
confidence: 99%
“…4 While the synthesis, processing, and applications of III-V materials have been studied for more than a decade, research on III-Sb NWs has attracted a growing interest only recently. [5][6][7][8][9] GaSb, in particular, is an increasingly important material for a III-V p-channel metaloxide-semiconductor field-effect transistor (MOSFET) due to its high hole mobility. 10 However, the mobility is highly dependent on the materials synthesis method and device structure.…”
mentioning
confidence: 99%
“…This is among one of smallest diameters obtained for GaSb nanowires/ nanopillars. 22,24,30 The aspect ratio of these nanopillars was estimated to approximately 24, which is larger than the previously reported top-down etched GaSb nanopillars with silica, 25 Au, 24 and resist 23 masks. The high resolution TEM (HRTEM) image and the corresponding fast Fourier transform (FFT) of a representative nanopillar show that the nanopillar has a diameter of 18.2 nm and a zinc blende crystalline structure ( Figure 1e).…”
mentioning
confidence: 94%
“…Yang et al reported the growth of GaSb nanowires on Si substrates using CVD. However, these GaSb NWs were coil-like and became intertwined, which made device fabrication difficult [70]. A. H. Chin used GaSb subwavelength wires with a cross-sectional dimension of 700-1500 nm and lengths of 10-70 µm to lase at approximately 1550 nm, as shown in Figure 12 [71].…”
Section: Low-dimensional Nanostructures Of Gasb Materialsmentioning
confidence: 99%